Viral suppression and viral rebound among young adults living with HIV in Canada. Issue 22 (June 2018) - Palmer, Alexis; Gabler, Karyn; Rachlis, Beth; Ding, Erin; Chia, Jason; Bacani, Nic; Bayoumi, Ahmed M.; Closson, Kalysha; Klein, Marina; Cooper, Curtis; Burchell, Ann; Walmsley, Sharon; et al.
Abstract : Abstract: Describe the prevalence and covariates of viral suppression and subsequent rebound among younger (⩽29 years old) compared with older adults. A retrospective clinical cohort study; eligibility criteria: documented HIV infection; resident of Canada; 18 years and over; first antiretroviral regimen comprised of at least 3 individual agents on or after January 1, 2000. Viral suppression and rebound were defined by at least 2 consecutive viral load measurements <50 or >50 HIV-1 RNA copies/mL, respectively, at least 30 days apart, in a 1-year period. Time to suppression and rebound were measured using the Kaplan–Meier method and Life Table estimates. Accelerated failure time models were used to determine factors independently associated with suppression and rebound. Younger adults experienced lower prevalence of viral suppression and shorter time to viral rebound compared with older adults. For younger adults, viral suppression was associated with being male and later era of combination antiretroviral initiation (cART) initiation. Viral rebound was associated with a history of injection drug use, Indigenous ancestry, baseline CD4 cell count >200, and initiating cART with a protease inhibitor (PI) containing regimen. The influence of age on viral suppression and rebound was modest for this cohort. Our analysis revealed that key covariates of viral suppression and rebound for young adults in Canada are similar to those of known importance to older adults. Women, people who use injection drugs, and people with Indigenous ancestry could be targeted by future health interventions.